2010
DOI: 10.15420/ecr.2010.6.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Computed Tomography Coronary Angiography Scan – Advantages and Disadvantages of Different Post-processing Techniques

Abstract: Computed tomography coronary angiography (CTCA) is increasingly performed worldwide. For the interpretation of the acquired data set, different post-processing techniques are available, such as multiplanar reformation, maximum-intensity projections, direct volume rendering, virtual coronary angioscopy or the angiographic view. Each of these techniques shows certain advantages and disadvantages during application and image interpretation. Thus, a combination of post-processing techniques for the interpretation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Moreover, bifurcation angle alteration is important in the development of atherosclerosis: the larger the bifurcation angle, the more turbulence and hemodynamic impact in the arterial wall 44 . In a study conducted by Ghafar et al, it was observed that the bifurcation angle was significantly associated with the presence of atherosclerotic plaques at the bifurcation site, with an average angle of 77.32 ± 18.1° compared to 62.24 ± 18.2° in the control group 30 . Moon et al suggested that angles greater than 60° between the LAD artery and LCX artery were indicative of a higher presence of atherosclerotic plaques, with a p ‐value of 0.058 27 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, bifurcation angle alteration is important in the development of atherosclerosis: the larger the bifurcation angle, the more turbulence and hemodynamic impact in the arterial wall 44 . In a study conducted by Ghafar et al, it was observed that the bifurcation angle was significantly associated with the presence of atherosclerotic plaques at the bifurcation site, with an average angle of 77.32 ± 18.1° compared to 62.24 ± 18.2° in the control group 30 . Moon et al suggested that angles greater than 60° between the LAD artery and LCX artery were indicative of a higher presence of atherosclerotic plaques, with a p ‐value of 0.058 27 .…”
Section: Discussionmentioning
confidence: 99%
“…44 In a study conducted by Ghafar et al, it was observed that the bifurcation angle was significantly associated with the presence of atherosclerotic plaques at the bifurcation site, with an average angle of 77.32 ± 18.1°compared to 62.24 ± 18.2°in the control group. 30 Moon et al suggested that angles greater than 60°between the LAD artery and LCX artery were indicative of a higher presence of atherosclerotic plaques, with a p-value of 0.058. 27 Juan et al identified a notable discrepancy in bifurcation angles only among groups with more than 50% stenosis compared to those with unremarkable stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations